PENDAMPINGAN ORANG TUA DAN GURU PAUD DALAM PERKEMBANGAN DAN PENDIDIKAN ANAK DI KEPULAUAN SERIBU UTARA, KEPULAUAN SERIBU PROVINSI DKI JAKARTA - Hanifa, Fadiya Dina; Hapsari, Kurnia Mega (Yayasan Nusantara Hasana Berdikari, 2025)
The Golden Age phase is the most important stage in a child's development. In this phase, physical and psychological functions mature which allows the child to respond optimally to stimulation from the environment. This period is also the basis for developing cognitive, motor, language and social-emotional abilities, which will later support children's learning process at school. Unfortunately, not all parents realize that at the PAUD (Early Childhood Education) level, training and developing cognitive, motor, language and social-emotional skills is much more important than just focusing on reading, writing and arithmetic skills. This understanding is really needed by parents and teachers in order to prioritize children's development in early childhood. Currently, some parents and teachers in the Thousand Islands still do not understand the stages of child development which include sensory, motor, language, cognitive and social-emotional aspects during early childhood. As a result, children's potential is not trained and optimized properly. Therefore, solutions are needed to increase parents' understanding regarding children's development and education. The methods used in this research include initial surveys, FGD implementation, and problem analysis. The research results show that there are still many teachers and parents who do not understand the importance of stimulating children's development holistically, so training and mentoring are necessary solutions to increase their capacity to support early childhood development.